Letramento digital na formação inicial docente: uma análise da percepção e atuação dos coordenadores de cursos de Licenciatura das universidades públicas brasileiras para a construção de bases para o desenvolvimento de competências digitais - Ribeiro, Luis Eduardo Eugenio (2023)
This research aims to analyze the perception and actions of coordinators of teacher training courses for Elementary and High School (Licenciatura) from public universities regarding the role of technology and digital literacy in the realm of teaching, specifically during the initial training period. The research seeks to address the following hypotheses: is appropriate digital literacy necessary for teachers? Is the initial training period the ideal opportunity for this learning? Are there a variety of tools, platforms, and contexts recommended as possible foundations for the development of digital skills? Through the responses from 215 course coordinators across all areas of knowledge and states from an online questionnaire, a solid positive agreement was obtained for all the raised hypotheses, including the proposed foundations, regardless of the tested segmentations. A direction for adding or revising the presented foundations in public policies for teacher training is suggested